An empirical research of the factors affecting users to follow companies' microblogs. (1st January 2014) - Zhang, Kem Z.K.; Zhao, Sesia J.; Zhang, Hong; Lee, Matthew K.O.
A number of companies have been creating accounts on microblogging sites to promote products/brands and communicate with customers. In this study, we attempt to understand the factors that may drive online users to follow companies' microblogs. We develop a research model through the perspective of elaboration likelihood model. Users' following behaviour is explained through three levels of participation: reading messages, forwarding messages and commenting on messages of companies' microblogs. We propose that information quality and source credibility are two key antecedents in the model. In addition, we extend the model by considering the impact of similarity on users' following behaviour. We empirically test our model by collecting data from an existing microblogging site in China. The results show that most of the hypotheses are supported. Implications for both theory and practice are discussed.